Correlation between presbycusis with quality of life based on hearing handicap inventory for the elderly screening version (HHIE-S) - Nazarudin, Nurbaiti; Priasty, Vania Nanda; Ma’mur, Iwan Darmawan (ACTA Medical Health Sciences, 2022)
Presbycusis is an age-related hearing loss caused by a degeneration process which is a cumulative effect of various risk factors. Hearing Handicap Inventory for the Elderly-Screening version (HHIE-S) questionnaire is a questionnaire that can be used to measure the quality of life in patients with hearing loss. This study aimed to determine the relationship between presbycusis with the quality of life. The research uses cross sectional analytical research methods. The data used in form of primary data is the result of filling in the guided questionnaire and the results of the audiogram, while secondary data is in the form of medical records of presbycusis patients at Dustira Hospital in the period January 2017-December 2018. Data were analyzed by Chi-Square and Spearman Correlation Test. The incidence of presbycusis in the period January 2017-December 2018 at Dustira Hospital was 2,6%. The result showed most of the patients were 65-74 years old (61,8%), male (52,7%), married (58,2%), economic were similar between moderate and low economic status (49.1%), had a history of chronic diseases (76, 4%), had a moderate degree of hearing loss (61,8%) and had a mild-moderate degree of quality of life (52,7%). Based on HHIE-S questionnaire the results showed that there was a significant and strong relationship between presbycusis and patients’ quality of life (p <0.001) and r=0,509. In conclusion, degrees of hearing loss in presbycusis patients will correspond to degrees of decrease in quality of life. DOI : 10.35990/amhs.v1n2.p54-63 REFERENCES Kementerian Kesehatan Republik Indonesia. Gambaran kesehatan lanjut usia di Indonesia. Buletin Jendela Data dan Informasi Kesehatan: Kementerian Kesehatan RI; 2013: 27-39. Suhartin P. Teori penuaan, perubahan pada sistem tubuh dan implikasinya pada lansia. Semarang: Fakultas Kedokteran Universitas Diponegoro; 2010. Ballenger JJ, Snow JB. Ballenger’s Otorhinolaryngology Head and Neck Surgery. 16th ed. BC Decker Inc. Spain; 2003: 443-454. Suwento R, Hendarmin H. Gangguan pendengaran pada geriatri. Dalam: Soepardi EA, Iskandar N, Bashiruddin J, Restuti RD, Eds. Buku Ajar Ilmu Kesehatan Telinga Hidung Tenggorok Kepala & Leher. Ed 7. Jakarta: Balai Penerbit FKUI, 2016: 36-38. Ardan, Juliarti. Sinopsis Ilmu Kesehatan Telinga Hidung Tenggorok. Bangka Belitung: Penerbit Buku Kedokteran AFJ; 2008: 15-18. Lalwani AK. Current Diagnosis & Treatment. 3rd ed. LANGE; 2012: 689-967. World Health Organization (WHO). Millions of people in the world have hearing loss that can be treated or prevented. 2013. Kementerian Kesehatan Republik Indonesia. Pendengaran sehat untuk hidup bahagia; 2013. Kementerian Kesehatan Republik Indonesia. Telinga sehat pendengaran baik; 2010. Hoffman HJ, Dobie RA, Losonczy KG, Themann CL, Flamme GA. Declining prevalence of hearing loss in US adults aged 20 to 69 years. JAMA; 2017; 143(3): 274-285. Badan Penelitian dan Pengembangan Kesehatan Kementerian Kesehatan RI. Riset kesehatan dasar (Riskesdas 2013). Kementerian Kesehatan Republik Indonesia, Jakarta; 2013: 243-245. Dina, L. Prevalensi presbikusis dan faktor risiko yang mempengaruhi lanjut usia di Balai Perlindungan Sosial Provinsi Banten. Jakarta: Fakultas Kedokteran dan Ilmu Kesehatan Universitas Islam Negeri Syarif Hidayatullah; 2013. Astari NL. Uji diagnostik HHIE-S versi Indonesia untuk skrining gangguan pendengaran usia lanjut. [Tesis]. Denpasar: Program Pascasarjana Universitas Udayana; 2014. Muthmainnah D. Hubungan presbikusis dengan depresi pada lansia di Poliklinik THT RSUD Dr. Zainoel Abidin Banda Aceh. [Tesis]. Darussalam Banda Aceh: Fakultas Kedokteran Universitas Syiah Kuala; 2014. Nurbaiti Nazarudin, et al. Kualitas hidup lansia. Jurnal Keperawatan, ISSN 2086-3071; 2012. WHO. Programme on mental health: WHOQOL user manual. Geneva: World Health Organization; 2012. Salim OC, Sudharma NI, Kusumaratna RK, dan Hidayat A. Validitas dan reliabilitas World Health Organization quality of life – Bref untuk mengukur kualitas hidup lanjut usia. Jakarta: Jurnal Universa Medika; 2007; 26(1). Wikanada G. Hubungan kualitas hidup dan faktor risiko pada usia lanjut di wilayah kerja puskesmas Tampaksiring I Kabupaten Gianyar Bali. Intisari Sains Medis; 2017; 8: 41-49. Istiqomah SN, Imanto M. Hubungan gangguan pendengaran dengan kualitas hidup lansia. Majority, 2019; 8(2): 234-239. Aktarabay K. Hubungan fungsi pendengaran dengan kualitas hidup pasien gangguan dengar di Poliklinik THT-KL RSUD ZAB Banda Aceh. Darussalam Banda Aceh: Fakultas Kedokteran Universitas Syiah Kuala; 2018. Nordvik O, Laugen Heggdal PO, et al. Generic quality of life in persons with hearing loss: A systematic literature review. BMC Ear, Nose and Throat Disorders; 2018; 18(1): 1-13. Lazzarotto S, Baumstrack K, Auqueir P. Age-related hearing impairment and impact on quality of life: A review of available questionnaires. Ann Otolaryngol Rhinol. Paris; 2016; 3(5): 1107:1-8. Said EA. Health-related quality of life in elderly hearing aid users vs. non-users. Egyptian Journal of Ear, Nose, Throat and Allied Sciences; 2017; 18: 271-279. Djamin R. Kualitas hidup lansia dengan gangguan pendengaran. Makasar: Laporan penelitian bagian Ilmu Kesehatan Telinga Hidung Tenggorok; 2010. Gondodiputro S, Hidayari AR, Rahmiati L. Gender, age, marital status and education as predictors to quality of life in elderly: WHOQOL-BREF Indonesian version. Department of Public Health, Faculty of Medicine University Padjajaran. Bandung. 2018. Fatmawati R, Dewi YA. Karakteristik penderita presbiakusis di Bagian Ilmu Kesehatan THT-KL RSUP Dr. Hasan Sadikin Bandung periode Januari 2012 - Desember 2014. [Tesis]. Departemen Ilmu Kesehatan Telinga Hidung Tenggorok Bedah Kepala dan Leher, Fakultas Kedokteran, Universitas Padjadjaran / Rumah Sakit Hasan Sadikin Bandung. 2015. Megari, K. Quality of life in chronic disease patients. Health Psychology Research. Italy. 2013: 141-148. Nazarudin N, Kristianti A, Nurrokhmawati Y. Pemeriksaan pendengaran: Pemeriksaan audiometri dan murni. Dalam: Nataliningrum RDM, Pratiwi ST, Djajasasmita D, Kristianti A, Handayani DR, editors. Buku pedoman praktikum (BPP) Blok 20 Kedokteran Kerja. FK Unjani. Cimahi; 2018: 33-38. Purnami N, Mulyaningsih EF, Ahadiah TH, Utomo B, Smith A. Score of hearing handicap inventory for the elderly (HHIE) compared to whisper test on presbycusis. Indian J Otolaryngol Head and Neck Surg; 2020: 1-5. https://doi.org/10.1007/s12070-020-01997-5.